Nutrition for the high‐risk surgical patient, when they need it most: Question and answer session. (5th December 2022) - Morrison, Chet; Prado, Carla M.; Wischmeyer, Paul; Martindale, Robert G.; Pimiento, Jose; Katz, Jennifer; Mechanick, Jeffrey I.; Patel, Jayshil J.
Abstract: Patients requiring complex or extensive surgery are often at high risk for perioperative and postoperative nutrition risk. Despite published guidelines, providing adequate nutrition to these patients continues to remain a clinical challenge. Using the case of a patient with preoperative nutrition risk who will need to undergo timely cancer resectional surgery, speakers presenting at the American Society for Parenteral and Enteral Nutrition 2022 Preconference discussed novel strategies to assess for nutrition risk, enhanced recovery after surgery, and preoperative and postoperative nutrition management in these often complex surgical patients.